Preparation and study of low-resistance polyacrylonitrile nano membranes for gas filtration. Issue 2 (January 2017) - Lou, Li-Hua; Qin, Xiao-Hong; Zhang, Hongnan
In this paper, patterned nanofibrous membranes were fabricated for air filtration. Polyacrylonitrile was employed as the electrospinning material as its fluffy property and bulged bubble template served as collector to prepare the patterned membrane. With this special structure, the pressure drop significantly declined from 151.7 to 24.7 mmH2 O, although the filtration efficiency of nanofiber membranes exhibited a slight decline from 99.94% to 96.33% compared to traditional electrospinning nanofibrous membranes. These sharp declines of the pressure drop while retaining the filtration efficiency imply that it could have more extensive applications.